The suspicions of Mr. Whicher A shocking murder and the undoing of a great Victorian detective - Summerscale, Kate 1965-
In June of 1860 three-year-old Saville Kent was found at the bottom of an outdoor privy with his throat slit. The crime horrified all England and led to a national obsession with detection, ironically destroying, in the process, the career of perhaps the greatest detective in the land, Jonathan Whicher of Scotland Yard. Whicher quickly believed the unbelievable--that someone within the family was responsible for the murder of young Saville Kent. Without sufficient evidence or a confession, though, his case was circumstantial and he returned to London a broken man. Though he would be vindicated five years later, the real legacy of Jonathan Whicher lives on in fiction: the tough, quirky, knowing, and all-seeing detective that we know and love today ... from the cryptic Sgt. Cuff in Wilkie Collins's The Moonstone to Dashiell Hammett's Sam Spade.--From publisher description